On the convergence of solutions of the variational problems with integral constraints and degeneration in variable domains - Rudakova, O.A. (Труды Института прикладной математики и механики, 2013)
In this article we deal with a sequence of integral functionals defined on weighted Sobolev spaces associated with a sequence of n-dimensional domains. For the given functionals we consider variational problems with sets of constraints of an integral kind. We establish sufficient conditions of convergence of minimizers and minimum values of the variational problems under consideration.